Length of Women’s Stays in Domestic Violence Shelters: Examining the Contribution of Background Variables, Level of Violence, Reasons for Entering Shelters, and Expectations - Ben-Porat, Anat (Journal of interpersonal violence, 2021)
Women’s shelters are one of the most important services established for women who are victims of intimate partner violence against women (IPVAW). Studies indicate that women undergo positive processes in shelters, and the longer the stay in the shelter, the more successful the woman will be in leaving the cycle of violence. However, the literature also reveals a remarkable variance in the length of women’s shelter stays, and very little research has been conducted to understand the factors contributing to this variance. The current research focused on the contribution of demographics (ethnic origin, age, education, number of children, and employment situation), history of violence (level of violence, characteristics of violence, and separation attempts from the partner), reasons for entering the shelter, and expectations of the shelter framework to the length of women’s shelter stays. Research participants consisted of 506 women living in 12 shelters in Israel. The findings revealed a variance in the length of the women’s stays in accordance with their ethnic origins. Women who had immigrated to Israel from Ethiopia or from the former Soviet Union (FSU) stayed in shelters for longer periods of time than did Israeli-born Arab women, who stayed in shelters for significantly shorter periods of time than did Israeli-born Jewish women. There was no contribution of the demographic variables to the variance of length of the woman’s shelter stay. In addition, previous separations, emotional abuse, and applying to the shelter following the decision of a child protection worker explained 12% of the variance in the length of the woman’s shelter stay. The findings point to a specific profile that seems to predict a woman’s longer stay in shelters for women who are victims of intimate partner violence.